Prevalence and Risk Factors for Rapid Eye Movement-Related Obstructive Sleep Apnea in Children - Chamnanpet, Surisa; Tovichien, Prakarn; Tanphaichitr, Archwin; Chotinaiwattarakul, Wattanachai (Frontiers in Pediatrics, 2022)
Objectives: Different pathophysiological mechanisms and the distribution of respiratory events among rapid eye movement (REM) and non-rapid eye movement (NREM) sleep modulate the effect of obstructive sleep apnea (OSA). We aimed to study the prevalence and risk factors for REM-related OSA in children. Study design: Retrospective, cross-sectional study Methods: We recruited 366 children with OSA confirmed by polysomnography (PSG) over a 5-year period. REM-related OSA is defined by an obstructive apnea-hypopnea index (OAHI) in the REM sleep ≥ 2 x than during NREM sleep. Results: The prevalence of REM-related OSA in children was 50.3%. Children with REM-related OSA were more likely to be female (P = 0.042), and had lower prevalence of adenotonsillar hypertrophy (P = 0.043) compared with children with other OSA subtypes. Children with REM-related OSA slept longer in the supine position (P = 0.003), had shorter duration of NREM1 sleep (P = 0.018), lower nadir SpO2 (P = 0.005), and a higher oxygen desaturation index 3% (ODI3%) (P = 0.014) compared with other OSA subtypes. Female gender and supine sleep was the independent risk factors for REM-related OSA. Conclusions: The prevalence of REM-related OSA was 50.3%. OAHIREM should be considered as an important parameter in future clinical research studies done in children with OSA.